MODEL KOMUNIKASI PADA PENYULUHAN PERTANIAN BERBASIS COOMUNITY DEVELOPMENT (STUDI LAPANGAN DI DINAS PERTANIAN DAERAH KABUPATEN JENEPONTO) - Yuliana Yuliana; Abd Majid; Muhammad Ilham (UNIVERSITAS MUSLIM INDONESIA, 2020)
This research is studt about the application of Laswell’s communication model theory by agricultural extension officers in activity of community development, for farmers in the region of Kab. Jeneponto. The purpose of this stuy to find out the theory of the communication model applied by agricultural extension officers to the community in the Kab. Jeneponto and to understand the acceptance of the community on the communication model of counseling in community development activities in the Kab. Jeneponto. The result of this study that the application of the theory of communication models applied by agricultural extension officers to the community in the Kab. Jeneponto, based on research conducted by the author, suggests that agricultural extension officers in the field have similarities with Lasswell's communication model. Because it includes five elements in the Lasswell model, namely: Who (who); What (what); Channels (media); Whom (who); Effect (effect). Public acceptance of the extension communication model in community development activities in the district. Jeneponto, namely agricultural extension in the sense of community empowerment, is a momentum for extension workers to be closer to the community, so that farmers and the community in general can obtain information about the development of agricultural technology in particular and social development in general. Agricultural technology information can provide economic and social benefits for farming communities. This study using qualitative metodes, sources of data used are primary and secondary data; primary data is a source of data obtained directly using the method. While secondary data is a source of data obtained through books and research journals.